Investigating the Effect of Laser Wavelength and Environment on the Synthesis of Copper and Copper Oxide Nanoparticles by Nanosecond Nd:YAG Laser in Liquid - H. Naderi-Samani; R. Shoja Razavi; R. Mozaffarinia (Journal of Advanced Materials in Engineering)
In this research, copper nanoparticles were synthesized via laser ablation in liquid using a nanosecond Nd:YAG laser. First, the effect of wavelengths of 532 nm and 1064 nm on the synthesis of copper nanoparticles in acetone and distilled water was investigated. After finding the appropriate wavelength, the effect of synthesis media in the presence of surfactants containing cetyltrimethylammonium chloride, sodium dodecyl sulfate, and polyvinyl pyrrolidone on copper nanoparticles was studied. Visible-ultraviolet optical spectroscopy, atomic absorption spectroscopy, dynamic light diffraction, and field emission scanning electron microscopy were employed to investigate the optical properties, synthesis efficiency, size, and morphology of copper nanoparticles prepared by the laser ablation in liquid method, respectively. The results showed that copper nanoparticles could be successfully synthesized in an acetone medium at 1064 nm wavelength. Also, due to the formation of copper oxides instead of copper nanoparticles, there is a slight possibility of preparing copper nanoparticles in aqueous environments.